A non-invasive luminescent nano-thermometer: approaching the maximum thermal sensitivity of Er3+ ion's green emission. Issue 21 (8th May 2019) - Li, Leipeng; Qin, Feng; Zhang, Zhiguo
Abstract : The maximum relative thermal sensitivity for the green luminescence of the Er 3+ ion is reported. Abstract : The green luminescence of the Er 3+ ion, ascribed to the 2 H11/2 / 4 S3/2 – 4 I15/2 transitions, has been a useful tool for optical ratiometric thermometry for more than thirty years. However, its relative sensitivity is relatively low, being ca. 1.1% K −1 at room temperature. To boost the sensitivity for this pair of transitions, here a non-invasive luminescent nano-thermometer, that is, Y2 O3 :Yb 3+, Er 3+, is designed by a co-precipitation method. Its maximum sensitivity is as high as 1.51% K −1 at 303 K, following the 980 nm laser diode excitation. The value is, to the best of our knowledge, larger than most previously reported relative sensitivities for the green luminescence of Er 3+ ions embedded in a variety of hosts. It is then demonstrated that the achievement of this maximum sensitivity should be ascribed to the following two factors. For one thing, the Y2 O3 host leads to a larger energy gap for the 2 H11/2 / 4 S3/2 states ( ca. 1000 cm −1 ) than other reported hosts ( ca. 700 cm −1 ). For another, the relative sensitivity for the 523/562 nm emission bands is larger than that for the 550/562 nm ones by one order of magnitude, indicating that choosing a pair of suitable transitions is important. A high temperature resolution (0.06 K) and an excellent repeatability (98.9%) are achieved for the designed nano-thermometer. The nano-thermometer is then used to monitor the temperature fluctuation of the home-made heating chamber set at 303 K and a good result is obtained. More importantly, hard evidence is provided here to show the importance of boosting the relative sensitivity on designing new types of nano-thermometers.